PEMBUATAN LIP BALM BERBASIS PARAFFIN WAX DENGAN EKSTRAK DAUN MANGGA SEBAGAI NILAI SPF - Nur Sadrina Darayani; Bagas Dwi Pangestu; M. Syifa Zainur Anwar; Najwa Kamila Widodo; Asa Aditya Persada; Aditya Dharmawan (Jurnal Riset Multidisiplin Edukasi, 2026)
There is increasing public awareness of the importance of protecting lips from sun exposure (ultraviolet rays, UV), pollution, and extreme temperatures. Lips are more susceptible to dryness and damage due to UV exposure, because they do not have oil glands, so when lips are dehydrated or lack fluids they are more easily injured. Therefore, this study aims to obtain a lip balm formulation based on paraffin wax with the addition of mango leaf extract (Mangifera indica L.) as a natural active ingredient for SPF value. This research method uses a quantitative experimental approach, with testing of physical characteristics (organoleptic, homogeneity, spreadability, physical stability, and hedonic) to obtain the effectiveness of the final product. The study found that the lip balm made has a soft, non-sticky, even texture, and remains stable even after being stored for 21 days at room temperature. The best formula was found with a mixture of 25% paraffin wax and 5% beeswax, which also received the highest rating. According to research by Cahyani, Rusydi Hashim, and Pramestyani (2024), mango leaf extract at a concentration of 10,000 ppm achieved an SPF of 37.1, which is considered high protection. Thus, the combination of paraffin wax and mango leaf extract produces a stable, effective lip balm with the added benefit of natural UV protection.